2011
DOI: 10.1016/j.jamcollsurg.2011.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age on Quality Measure Adherence in Colon Cancer

Abstract: BACKGROUND Recently lymph node yield (LNY) has been endorsed as a quality measure of CC resection adequacy. It is unclear whether this measure is relevant to all ages. We hypothesized that total lymph node yield (LNY) is negatively correlated with increasing age and overall survival (OS). STUDY DESIGN The Surveillance, Epidemiology and End Results (SEER) database was queried for all non-metastatic CC patients diagnosed from 1992–2004 (n=101,767), grouped by age (<40, 41–45, 46–50, and in 5-year increments un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
10
25
1
Order By: Relevance
“…The largest study, comprising 47 455 patients in Great Britain and Ireland, had a stage distribution similar to the present results [2]. A smaller lymph node yield in the elderly has been described in previous publications [3,12]. Steele et al [3] found a 3.4% decrease in lymph-node yield for each 5-year interval between the ages of 40 and 86 years or more.…”
Section: Cancer Stage and Lymph Node Pathologysupporting
confidence: 89%
“…The largest study, comprising 47 455 patients in Great Britain and Ireland, had a stage distribution similar to the present results [2]. A smaller lymph node yield in the elderly has been described in previous publications [3,12]. Steele et al [3] found a 3.4% decrease in lymph-node yield for each 5-year interval between the ages of 40 and 86 years or more.…”
Section: Cancer Stage and Lymph Node Pathologysupporting
confidence: 89%
“…51 a decline in ln number with advancing age has been described in nondiseased lns and in the context of colon cancer. 5,17,30,52 in the present study, no correlation was found between ln number and age, but because the cadavers were all aged more than 74 years, this relationship cannot be adequately tested. Low-power photomicrographs of lymph nodes from sigmoid mesocolon stained with H&E illustrating focal lipomatosis involving less than 50% of lymph node (A), diffuse lipomatosis involving more than 50% of the lymph node (fibrous capsule visible in adjacent section) (B), and multiple fluid-filled cavities in the medullary zone (C and D).…”
Section: Discussioncontrasting
confidence: 55%
“…1 according to the surveillance epidemiology and end Result database, from 2000 to 2008, there was a 10% overall increase in CRC, with the largest proportion in those <50 years of age versus a 20% decrease in those >50 years of age. 2,3 some studies suggest that young patients with CRC have a relatively worse prognosis, but others suggest that young patients' survival is equivalent to older individuals when risk-adjusted for comorbid variables. [4][5][6] Contributing factors to age-associated disparities in CRC outcomes have included problems with access to health care, delays in diagnosis, treatment, and follow-up differences.…”
mentioning
confidence: 99%